KARAKTERISTIK PENDERITA HERNIA INCARCERATA YANG DIRAWAT INAP DI RSUD Dr. PIRNGADI KOTA MEDAN TAHUN 2011 - Sari Purnama Yazid; Sori Muda Sarumpaet; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Incarcerated hernia is one kind of hernia that can not be repositioned into the abdominal cavity. According to WHO (2005), incarcerated hernia is one acute abdominal disease with the incidence of incarcerated hernia occurs approximately 6-10% of indirect inguinal hernia in adults and 14-56% in the femoral hernia. To know the characteristics of patients with incarcerated hernia who take care at RSUD Dr. Pirngadi Medan in 2011, conducted research with a descriptive case series design. The study population was as much as 121 cases, with a sample of the entire population (total sampling) and analyzed with Chi-square Fisher Exact, Mann-Whitney, and ANOVA test. The result of study is found the highest proportion of patients with hernias incarcerated characteristics: age> 60 years (24.8%), male (86.8%), sex ratio 625 or 6.57 (7): 1, Islam (72.7%), education senior high school (56.2%), occupation self-employed (43.8%), marital status married (68.6%), residence in Medan (81.0%), the main complaint of remain lumps + painful + constipation (52.9%), the location of hernia incarceration hernia inguinal (88.4%), maintainability long on the average 5.41 days with SD = 3,172 days, the cost sources JPKMS (36.4%), while come back of home with condition recover (50.4%), there are significant difference proportions between the sexes based on the location of the hernia had incarceration (p = 0.021), Chi-square test can not be used to see the difference proportions between the sexes based on while come back of home, the ages based on the location of the hernia had incarceration, there are significant difference the average long care based on costs source (p=0.003);based on the while come back of home (p = 0.000). To the public suffer hernia disease if it looks a lump that can not go back or signs indicating incarcerated hernia immediately went to the hospital or doctor in order to avoid a more severe condition. The health professionals are expected to provide health education to the community about hernia disease through health centers, neighborhood health center so that people know what action to be done. Keywords: Characteristics, Incarcerated Hernia, RSUD Dr.Pirngadi